2020
DOI: 10.3390/app10144960
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels Obtained via γ-Irradiation Based on Poly(Acrylic Acid) and Its Copolymers with 2-Hydroxyethyl Methacrylate

Abstract: Hydrogels containing both carboxyl and hydroxyl functional groups have been prepared by γ-irradiation of either aqueous solutions of acrylic acid (AA) and mixtures of AA and 2-hydroxyethyl methacrylate (HEMA) in different ratios, or aqueous solutions of poly(AA), PAA, and poly(AA-co-HEMA) obtained via solution polymerization. A higher absorbed dose is required in order to prepare hydrogels from monomer solutions, compared with those from polymer solutions. The range for the absorbed doses was chosen so that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…For exemplification, in Figure 4 a the DSC thermograms obtained for three xerogels (PAM4, 6, and 10) are plotted and they show minor differences in glass transition temperatures. Our previous study [ 33 ] on chemically crosslinked PAA and PAA copolymers obtained via gamma-irradiation showed that both DSC and TG curves were influenced by the absorption dose of radiation, i.e., by the degree of crosslinking. But unlike the gamma irradiation-induced crosslinking, when some additional chemical transformations such as partial decarboxylations accompanied the crosslinkages formation directly between the polymer chains [ 33 ], in this case the crosslinking process was mediated by BIBr having an overall flexible structure able to preserve almost the same local mobility of the polymer chains in the newly formed network irrespective of the BIBr content or even when compared to the uncrosslinked system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For exemplification, in Figure 4 a the DSC thermograms obtained for three xerogels (PAM4, 6, and 10) are plotted and they show minor differences in glass transition temperatures. Our previous study [ 33 ] on chemically crosslinked PAA and PAA copolymers obtained via gamma-irradiation showed that both DSC and TG curves were influenced by the absorption dose of radiation, i.e., by the degree of crosslinking. But unlike the gamma irradiation-induced crosslinking, when some additional chemical transformations such as partial decarboxylations accompanied the crosslinkages formation directly between the polymer chains [ 33 ], in this case the crosslinking process was mediated by BIBr having an overall flexible structure able to preserve almost the same local mobility of the polymer chains in the newly formed network irrespective of the BIBr content or even when compared to the uncrosslinked system.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the overlap of the TG thermograms, only the differences in the relative amounts of residue resulted after the degradation completed could be noticed ( Figure 4 b). Contrarily, in the case of PAA crosslinked via gamma-irradiation, there was no difference between the relative amount of the residue obtained after degradation of uncrosslinked and crosslinked polymers [ 33 ]. As the content of BIBr increases in copolymers from PAM2 to PAM10, a less relative amount of residue (from PAA to PAM10) results upon polymers degradation.…”
Section: Resultsmentioning
confidence: 99%
“…In this SLR, we also obtained the analysis of interpreted Tg using equation (1) depending on copolymerization. Micutz et al 41 reported that the two copolymers should exhibit a lower Tg than PAA. Specifically, equation (1) explains that Tg depends on the different molar ratio between monomers in the initial substrate.…”
Section: Resultsmentioning
confidence: 99%
“…The glass transition could vary depending on the molecule's polymerization degree and branching degree [42]. Accordingly, it seems that the polyglycerolbased copolymers exhibited two different glass transition temperatures that could be related to the different chain segments [43,44], contrary to the polyglycerol and PRE AA, which displayed a single glass transition temperature. Therefore, the glass transition temperature related to the polyglycerol segment of the polyglycerol-based materials increased according to the following trend: -73.19°C, -72.96°C, and -72.64°C for COP 30 w/w% AA+LA-5% AO, COP 30 w/w% AA+LA, and polyglycerol, respectively.…”
Section: Polymers Molecular Weightmentioning
confidence: 99%